Digital Literacy Global Framework Competence of Islamic Senior High School Students - Novia Ayu Sekar Pertiwi; Suci Prihatiningtyas; Siti Sukowati Wanafaktu Miruki; Ibrahim Yusuf Al Farros (SCHOOLAR: Social and Literature Study in Education, 2025)
This study aims to evaluate the level of digital literacy among students in Islamic Senior High School (MA) in Tembelang District, Jombang Regency, using the UNESCO Digital Literacy Global Framework (DLGF). The method employed is quantitative research with a cross-sectional survey design. The research sample consists of 40 students selected purposively. The analysis results indicate that overall, the students' digital literacy competencies fall into the good category, with an average of 69.75%. However, there is variation in competencies across the seven DLGF competency frameworks, with some aspects, such as the ability to assess information credibility and collaboration, requiring further attention. Recommended interventions include practical training and workshops to enhance students' digital competencies. This research is expected to provide a foundation for developing more effective interventions to improve digital literacy among Islamic Senior High School students.